Arm's-Length Intimacy: Employment As Relationship - Marion Crain (Washington University Journal of Law & Policy, 2011)
This Essay presents the importance of reconceptualizing employment as a relationship regarding money and love. It discusses the work law that ignores the realities of interdependence and mutual investment, commitment to a model of employment as an arm's length, and impersonal cash-for-labor transactions. Furthermore, the law draws distinctions between relationships, transaction, and on justifying the differential legal regime.
Keywords: Industrial relations; Employment at will; Human capital; Intimacy (Psychology); Contracts; Law & amp; economics; Collective bargaining; Employment terminations; Severance pay; Organizational behaviour; National Labor Relations Act